Influence of availability of shade on testicular characteristics of Santa Ines rams - doi: 10.4025/actascianimsci.v35i.18479 - Teodoro, Sônia Martins; Pereira, Alfredo Manuel Franco; Gusmão Filho, José Dantas; Silva, Jadir Nogueira da (Acta Scientiarum. Animal Sciences, 2013)
The purpose of this study was to evaluate the effects of availability of artificial shading on testicular and seminal characteristics of Santa Ines crossbred rams. Twelve 8 month old rams at 38.1 ± 5.2 kg average weight, were used in a total random design with two treatments: areas with and without available artificial shading (black polyethylene mesh screen for a 50% reduction of solar radiation). The scrotal circumference, scrotal length, scrotal volume, rectal temperature and scrotal temperature were measured twice a week. Also a biweekly analysis of the semen was carried out, measuring the volume and spermatic concentration as well as the percentage of normal spermatozoa. The results show that available shading provided for lower scrotal temperatures and higher sperm concentration, without influencing the scrotal volume and the percentage of normal spermatozoa. The testicular measures, such as the scrotal circumference and length were higher in the rams that were subjected to the no available shading treatment. The absence of differences, in some of the analyzed variables, between the two treatments, with and without available shading, could be due to high adaptability of the animals.